The Role of Teachers in the Formation of Students' Entrepreneurial Character at SMK Negeri 1 Polewali - Isgunandar, Isgunandar; Masdar, Patima; Nasrullah, Muh (Universitas Negeri Makassar, 2023)
The role of teachers in forming the entrepreneurial character of class x students at SMK Negeri 1 Polewali. This research aims to determine the role of teachers in forming the entrepreneurial character of class x students at SMK Negeri 1 Polewali. This research is quantitative research that shows cause and effect. The sample in this study was 51 students at Polewali State Vocational School 1 using a simple random sampling technique. The data collection techniques used are observation, questionnaires, and documentation. The data analysis techniques used in this research are descriptive data analysis and inferential statistical analysis. The research results show that the teacher's role is in the